2018
DOI: 10.1007/s11356-018-1663-5
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and histopathological effects of silver nanoparticles in rainbow trout (Oncorhynchus mykiss)—how about increase of salinity?

Abstract: Hematological and histopathological toxicities of silver nanoparticles (Ag-NPs) to rainbow trout were assessed in three water salinities: 0.4 ppt (low salinity), 6 ± 0.3 ppt (moderate salinity), and 12 ± 0.2 ppt (high salinity). The concentrations of Ag-NPs in the low salinity were 0.032, 0.1, 0.32, and 1 ppm, and in the moderate and high salinities were 3.2, 10, 32, and 100 ppm. The results indicated a concentration-dependently increased (thrombocyte, monocyte, and large lymphocyte) and decreased (neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…In our study, the monocyte levels in the fenugreek oil application groups were higher than the control group. Monocyte levels in phagocytic and lysosomal function-induced immune systems are as high as in our study groups (29,33). Monocyte increase, one of the representatives of the cellular immune response, was also found to be high in other studies performed with fenugreek (34).…”
Section: Discussionsupporting
confidence: 79%
“…In our study, the monocyte levels in the fenugreek oil application groups were higher than the control group. Monocyte levels in phagocytic and lysosomal function-induced immune systems are as high as in our study groups (29,33). Monocyte increase, one of the representatives of the cellular immune response, was also found to be high in other studies performed with fenugreek (34).…”
Section: Discussionsupporting
confidence: 79%
“…Different researches referred to the variability of pollutant effects on the biochemical indicators; such as AST, ALT, TP, Glu, Cr, and UA with an increase, decrease or no effect (Alkaladi et al, 2015;Imani et al, 2015;Joo et al, 2018;Rajkumar et al, 2016 ;Sayed and Authman, 2018;Shaluei et al, 2013). The pattern of adverse impacts in blood parameters may depend on fish species, age, stage of reproductive cycle and disease (Luskora, 1997) in addition to many environmental factors (Pandey, 1977) and seasonal conditions (Joshi and Tondon, 1977 ;Khan, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…For example, George et al (2014 ) observed that simulated solar light induced transformation of AgNPs (surface oxidation and Ag + release) and augmented their toxicity to zebrafish embryos. On the other hand, exposure medium containing a high concentration of chloride ions ( Groh et al, 2015 ) or higher salinity ( Kalbassi et al, 2011 ; Cáceres-Vélez et al, 2018 ; Joo et al, 2018 ) attenuated the acute and sublethal effects of AgNPs to zebrafish embryos and rainbow trout fry. Taken together, these findings suggest that laboratory conditions may over- or under-estimate the risk potential of ENM/Ps and demonstrate the need for carrying out toxicity tests under environmentally relevant exposure conditions.…”
Section: Aquatic Ecotoxicity Of Silver Nanoparticlesmentioning
confidence: 99%